Improving child nutrition for sustainable poverty reduction in Africa - Alderman, Harold; Behrman, Jere R.; Hoddinott, John F. (International Food Policy Research Institute, 2004)
While famines and other episodes of severe hunger receive significant press coverage and attract much public attention, chronic hunger and malnutrition are considerably more prevalent in Africa. It is estimated that 14 percent of children are born with low birthweights every year, around 45 million preschool children are malnourished, and 192 million Africans of all ages are hungry.... This brief argues that failing to give adequate attention to child nutrition issues is shortsighted if African governments seek sustainable reductions in poverty. In poorly nourished populations, reductions in hunger and improvements in nutrition provide considerable productivity gains and save resources that can then be used for other pressing investments. It is the existence of these sizeable gains together with the availability of cost-effective interventions that underlies the economic case for improving child nutrition in Africa." -- from Text